2023
DOI: 10.1111/cob.12588
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of lipoedema from bilateral lower limb lymphoedema by imaging assessment of indocyanine green lymphography

Abstract: Summary Lipoedema is characterized by disproportionate painful fat accumulation mostly in the lower limbs. The presence of lymphoedema in lipoedema remains controversial. This study aimed to assess the presence or absence of lymphoedema in the lower limbs of women with lipoedema using indocyanine green (ICG) lymphography. A cross‐sectional retrospective study was undertaken in women with a clinical diagnosis of lipoedema whose lower limbs were examined with ICG lymphography. MD Anderson Cancer Center (MDACC) I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 34 publications
0
2
0
1
Order By: Relevance
“…Four studies evaluated indocyanine green findings in lipedema (Table 8). 19,[37][38][39] These studies revealed significant changes in superficial lymph flow in lipedema with slower lymph flow, higher number of abnormal lymphatic vessels, and higher fluorescent intensity in the skin, 19 dilation of lymphatic vessels, intravascular pooling, and greater propulsion rates. 39 Overall, only three studies reported cutoff values for diagnosing lipedema, and five studies reported the diagnostic accuracy of imaging studies (Table 9).…”
Section: Study Characteristicsmentioning
confidence: 86%
“…Four studies evaluated indocyanine green findings in lipedema (Table 8). 19,[37][38][39] These studies revealed significant changes in superficial lymph flow in lipedema with slower lymph flow, higher number of abnormal lymphatic vessels, and higher fluorescent intensity in the skin, 19 dilation of lymphatic vessels, intravascular pooling, and greater propulsion rates. 39 Overall, only three studies reported cutoff values for diagnosing lipedema, and five studies reported the diagnostic accuracy of imaging studies (Table 9).…”
Section: Study Characteristicsmentioning
confidence: 86%
“…Among these, only two—the ipsilateral inguinal and popliteal regions—were original regions, while the remaining six were compensatory regions. The most common compensatory pathways include the contralateral inguinal region, identified in 13–30% of patients with cancer-related LLLE, followed by the gluteal pathway in 4–23% 16 , 17 .…”
Section: Lymphographymentioning
confidence: 99%
“…Unterstützend dazu quantifizierten Birkballe et al keine Unterschiede im lokalen Wassergehalt (Tissue Dielectric Constant TDC, n=10, ns ) der Probanden 47 . Mackie et al konnten das Lipödem ebenso nicht mit dem Vorhandensein eines Lymphödems in Verbindung bringen (Indocyaningrün Färbung, n=40) 48 .…”
Section: Ergebnisseunclassified